The impact of functional integration on the reliability of substation protection and control systems. - Castro Ferreira, L.R (IEEE Transactions on power delivery)
Reliability models and techniques created to assess the reliability of integrated substation protection and control systems are outlined. The technique is used to quantify the impact on reliability of integrated protection and control functions in a feeder bay within a National Grid Company (UK) 400 kV transmission substation. The results show that judicious integration of function leads to reliability gains, afforded by hardware rationalization